CO2 Emissions and Institutions: Moderating Role of Governance in Environmental Sustainability - Jelena Zvezdanović Lobanova; Mikhail Lobanov (Međunarodni Problemi)
The paper deals with the impact of institutional quality, as well as its interdependence with economic performance, on environmental degradation during the period from 2002 to 2021 for a panel of 27 transition countries. The main aim of the study is to investigate the interaction role of institutional quality on the association between economic growth, urbanization and CO2 emissions in selected countries. Based on the system Generalized Method of Moments estimation results,we find that overall institutional quality, as well as bolstering regulatory structures, strengthening of the rule of law, improving the control of corruption and enhancing government efficiency is positively associated with carbon emissions. The institutional advancement is conducive to economic expansion, which contributes to the deterioration of environmental quality. Our empirical findings reveal that the advancement in institutional framework together with economic expansion and urbanization augment environmental degradation. Given results have important policy implications, indicating that the institutional setting may cause trade-offs between promoting economic growth and the environmental protection.